2019
DOI: 10.1523/jneurosci.0881-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Degeneration Is Mediated by Necroptosis Activation

Abstract: Axonal degeneration, which contributes to functional impairment in several disorders of the nervous system, is an important target for neuroprotection. Several individual factors and subcellular events have been implicated in axonal degeneration, but researchers have so far been unable to identify an integrative signaling pathway activating this self-destructive process. Through pharmacological and genetic approaches, we tested whether necroptosis, a regulated cell-death mechanism implicated in the pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 99 publications
7
45
0
Order By: Relevance
“…It is interesting that we found the influence of Nec-1 on H 2 O 2 -evoked neurite shortening (Fig. 3d) which confirms in vivo findings on participation of necroptosis in axonal degeneration and suggests a possible therapeutic intervention by its inhibition by Nec-1 (Arrázola et al 2019). While this effect was observed in UN-SH-SY5Y at the late stage (18 h), in RA-SH-SY5Y cells, it was present at both studied time points (9 and 18 h) (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…It is interesting that we found the influence of Nec-1 on H 2 O 2 -evoked neurite shortening (Fig. 3d) which confirms in vivo findings on participation of necroptosis in axonal degeneration and suggests a possible therapeutic intervention by its inhibition by Nec-1 (Arrázola et al 2019). While this effect was observed in UN-SH-SY5Y at the late stage (18 h), in RA-SH-SY5Y cells, it was present at both studied time points (9 and 18 h) (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Several reports indicate that RIPK signaling contributes to neuronal loss in various in vivo mod-els (Ito et al 2016;Caccamo et al 2017;Yang et al 2017;Zhang et al 2017;Iannielli et al 2018). In some studies, RIPK1 has been shown to act directly in neurons to regulate degeneration (Re et al 2014;Iannielli et al 2018;Arrazola et al 2019), whereas others suggest that RIPK1 regulates necroptosis in other central nervous system cell types (Ofengeim et al 2015;Ito et al 2016). Interestingly, RIPK1 has also been shown to mediate a cell-autonomous proinflammatory response, rather than cell death, in peripheral immune cell populations and microglia (Najjar et al 2016;Ofengeim et al 2017;Yuan et al 2019).…”
Section: Evidence For Apoptosis Necroptosis and Other Death Pathwaymentioning
confidence: 99%
“…Genentech/Roche has advanced the first DLK inhibitor into clinical trials for ALS (NCT02655614), although results have not yet been reported. In the case of RIPK1, preclinical data from genetic models and mice treated with RIPK1 inhibitors, including necrostatin-1, suggest a potential role for RIPK1 signaling in a number of disease contexts, including AD, ALS, and multiple sclerosis (Re et al 2014;Ofengeim et al 2015Ofengeim et al , 2017Yang et al 2017;Arrazola et al 2019). Denali Therapeutics has recently advanced a CNS penetrant RIPK1 inhibitor into clinical trials, which is being tested in patients with AD and ALS (NCT03757325, NCT03757351).…”
Section: Cell Death and Neurodegenerationmentioning
confidence: 99%
“…This protective effect was also observed by genetic inhibition of Ripk3 or Mlkl. Notably, the loss of the electrophysiological nerve function was also prevented by blocking the necroptotic machinery (Arrázola et al, 2019). Furthermore, investigating the mechanisms of axonal degeneration in in vitro and in vivo models of Parkinson's disease, we also uncover the role of the necroptosis signaling pathway in this process.…”
Section: Necroptosis Involvement In the Mechanism Of Axonal Demisementioning
confidence: 88%
“…Despite the difference in timing, axonal degeneration in the context of both acute lesions and neurodegenerative diseases, share morphologic features that include axonal swelling, microtubule disruption, and fragmentation of neuronal processes (Wang et al, 2012), suggesting that they correspond to similar processes. Recent studies have shed light into the mechanisms that govern acute axonal degeneration, revealing the dependence of NAD + in this process, as well as the involvement of mitochondrial dysfunction and necroptosis activation (Barrientos et al, 2011;Osterloh et al, 2012;Neukomm et al, 2017;Hernández et al, 2018;Arrázola et al, 2019;Ko et al, 2020;Loreto et al, 2020;Oñate et al, 2020). Notably, all these pathways are associated to the hallmarks of aging (Kennedy et al, 2014;Sun et al, 2016;Deepa et al, 2018;Haas, 2019;Lautrup et al, 2019;Royce et al, 2019;McReynolds et al, 2020).…”
Section: Introductionmentioning
confidence: 99%